Torsional power study using CENTURION phacoemulsification technology. (22nd April 2016) - Jensen, Jason D; Shi, Dallas S; Robinson, Mark S; Kramer, Gregory D; Zaugg, Brian; Stagg, Brian C; Pettey, Jeff H; Barlow, William R; Olson, Randall J
Abstract: Background: To evaluate the effect of varying levels of power on phacoemulsification efficiency using the CENTURION Vision System. Methods: Formalin‐soaked porcine lenses were divided into 2‐mm cubes; 0.9‐mm, balanced tips were used. Torsional power levels were tested from 10% to 100% at 10% intervals. Vacuum was set to 550 mmHg, aspiration to 50 ml/min, and intraocular pressure at 50 mmHg. Efficiency (time to lens removal) and chatter (number of lens fragment repulsions from the tip) were determined. Results: Increasing torsional power up to 60% increased efficiency. This effect was linear from 30 to 60% power ( R 2 = .90; P < 0.05). There were no significant differences in efficiency past 60%. Chatter was highest at 10% power and decreased linearly ( R 2 = .87; P = 0.007) as power was increased up to 60% power, and chatter did not improve above this power level. Conclusions: Power improved efficiency only up to a 60% power level, and then was negligible. Chatter correlated well with power up to the 60% level, so that as power was increased, chatter decreased. Because there are no additional benefits in efficiency past 60% power, and because chatter is minimal at 60% power, we recommend torsional ultrasound at 60% as the optimal power setting for using the CENTURION System for phacoemulsification.l